Comparative performance of Khaki Campbell and Maithili ducks of Bihar under middle Gangetic plain (Indian Journal of Animal Production and Management, 2024)
An experiment was conducted to compare the performance of Khaki Campbell and Maithili ducks under  extensive system of management in middle gangetic plain (MGP) of Bihar where small water bodies are  available. Brooding of ducklings for one month was managed with commercial feed after which they were  exposed to free range management system. Leftover feed material and kitchen wastes were provided and  vaccination against duck plague was done in subsequent period. Growth and production performances,  mortality and egg quality data were recorded. The study revealed that Khaki Campbell ducks gained  significant body weight as compare to Maithili duck from day old to 24th week of age due to variation in  genotype. Attainment of early sexual maturity with significantly more egg production up to 40th week was  observed in Khaki Campbell whereas egg weight and other egg traits were better in native ducks. Egg  production rate of local native ducks (21.46 %) was found significantly lower (P
Keywords: Egg quality; Khaki Campbell; Maithili ducks; Performance